Rare crested rat subfossils unveil Afro–Eurasian ecological corridors synchronous with early human dispersals - (:unkn) unknown (My University, 2021)
Significance The extent and timing of paleoenvironmental connections between Africa and Eurasia during the last glacial and interglacial periods are key issues in relation to early dispersals of Homo sapiens out of Africa. However, direct evidence of synchronous faunal dispersals is sparse. We report the discovery near the Dead Sea of subfossils belonging to an ancient relative of the eastern African crested rat dated to between ∼42,000 and at least 103,000 y ago. Morphological comparisons, ancient DNA, and ecological modeling suggest that the Judean Desert was greener in the past and that continuous habitat corridors connected eastern Africa with the Levant. This finding strengthens the hypothesis that early human dispersals were prompted by climatic changes and Late Pleistocene intercontinental connectivity.
Keywords: African Research